2006
DOI: 10.1111/j.1475-6811.2006.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs and satisfaction in close relationships: The role of loss–gain framing

Abstract: Two studies were conducted to clarify the pattern of mixed results found in past research regarding the association between costs and satisfaction in close relationships. Insights from Prospect Theory (D. Kahneman & A. Tversky, 1979, 2000) suggested the importance of gain–loss framing in understanding costs. When costs are attached to valued outcomes, they are perceived as gains or investments; otherwise they are perceived as losses. Appreciation by one's partner for communal behaviors and family chores provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
2
18
0
3
Order By: Relevance
“…These results are consistent with other studies (e.g. A. R. Berger & Janoff-Bulman, 2006;M. Berger, Wagner, & Baker, 2005;Finn & Bishop, 2006;Gottlieb, 1981;Stokes & Wilson, 1984) that show that help is mobilized in a variety of ways depending on the contextual circumstances of the help that is required.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with other studies (e.g. A. R. Berger & Janoff-Bulman, 2006;M. Berger, Wagner, & Baker, 2005;Finn & Bishop, 2006;Gottlieb, 1981;Stokes & Wilson, 1984) that show that help is mobilized in a variety of ways depending on the contextual circumstances of the help that is required.…”
Section: Discussionsupporting
confidence: 82%
“…A great deal of research has examined this dilemma of reciprocity in the giving and receiving of help (e.g., Antonucci & Jackson, 1990;A. R. Berger & Janoff-Bulman, 2006;Fisher, Nadler, & Whitcher-Alagna, 1983;Reinhardt, Boerner, & Howowitz, 2006) and the burden that receiving help may imply.…”
Section: Discussionmentioning
confidence: 99%
“…They can help couples see even mundane tasks and activities as connecting behaviors. Other research has suggested that appreciation for a spouse's participation in doing mundane or routine tasks contributes to the closeness that spouses feel toward one another (Berger & Janoff-Bulman, 2006). As spouses give one another credit for contributing to the marriage, their appreciation for their spouse increases.…”
Section: Implications For Couple Therapymentioning
confidence: 97%
“…As spouses give one another credit for contributing to the marriage, their appreciation for their spouse increases. This appreciation then can lead to heightened satisfaction in the relationship (Berger & Janoff-Bulman, 2006). Couple therapists can help couples understand that shared meaning develops over time through the regular and persistent engagement in daily connecting behaviors.…”
Section: Implications For Couple Therapymentioning
confidence: 98%
“…From this perspective, the abused adolescent suffers various losses, including, but not limited to, her expectations about herself, her relationship, and the world; the loss of hope for a meaningful life; and the loss of security (Campbell, 1989;Turner & Shapiro, 1986). Operating on the assumption that grief is a normal response to significant losses, a counselor might validate that it is natural for a client to grieve for the losses she experiences (Berger & Janoff-Bulman, 2006;Campbell, 1989). Exploring and fully experiencing the grief associated with these losses, as well as the guilt associated with the choices that led to some of these losses, may serve as a catalyst for change for abused adolescent females.…”
Section: Freedommentioning
confidence: 99%